Feeding premature babies in the neonatology department of the Androva Mahajanga Hospital - Razanamanana, Safidisoa Nambinina; Raveloharimino, Nirina Henintsoa; Randriamanga, Radohery Lovasoa; Rabesandratana, Norotiana (International Journal of Contemporary Pediatrics, 2024)
Background: The initiation and progression of enteral nutrition in premature infants remains a challenge. The aim of this study was to evaluate enteral nutritional management in premature infants in the neonatology department at the mother and child complex Androva Mahajanga. Methods: This was a retrospective descriptive study over a 7-month period, from January to July 2018. All neonates under 37SA who received enteral feeding were included. Results: During the study period, 74 newborns were able to receive enteral feeding. The mean age of onset of enteral feeding was 10.6 hours. In 89.2% of cases, enteral feeding was started within the first 24 hours of life. On average, the initial quantity administered was 28.4ml/kg/d. Human milk was used most frequently (54.8%). The presence of residue was the most frequently encountered incident (31.5%). Ulcero-necrotizing enterocolitis occurred in 7 newborns (9.5%). Forty-five newborns had a good outcome, with an average weight gain of 9.28 g/kg/d. Conclusions: The implementation of a nutritional management protocol for newborns, especially premature babies, in the neonatology department would be beneficial for a better outcome and growth of the baby.